DA GÊNESE DAS CONTRADIÇÕES: a contradição capital-trabalho e a sociabilidade do cooperativismo popular - Ana Maria Marques Santos (Universidade Federal do Maranhão, 2014)
A new sociability cooperative work stands out today as conflicting movement, from the Genesis contradictions: a contradiction between capital and labour. This condition, onceived under a productive and distributive structural crisis gives an opening between other forms of organization, they, â new sociability dedicated to collective and solidarity. These points will become the focus of interest of the economy and the Administration, in order to know about a Report the man-worktechnology relations. Is made explicit in this way an intense and incursiva contradiction produces a our everyday reality in the expropriation of the workforce, and with it ownership and expropriation of cooperative work.